Determination of 180-Year Variation of Li Concentration in the Atmosphere using Corylus colurna L. Annual Rings - Key, Kübra; Kulaç, Şemsettin; Koç, İsmail; Şevik, Hakan (Prensip Publishing, 2023)
Environmental pollution has increased significantly in the current century due to various anthropogenic effects, especially industrial activities, mining, urbanization, and traffic. Significantly increasing air pollution has become a global problem that causes millions of people to die yearly. Heavy metals, the most dangerous and harmful components of air pollution, do not easily deteriorate and disappear in nature. They can be carried far from their source, tend to bioaccumulate in living organisms, and some can be toxic, carcinogenic, and fatal even at low concentrations for humans and animals. Therefore, monitoring the change of heavy metal concentrations in the air is critical. One of the most effective methods in determining the heavy metal concentration changes in the atmosphere from past to present is using annual rings of trees as biomonitors. In this study, the variation of Li concentrations, which is one of the most harmful heavy metals in terms of human and environmental health, in the last 180 years, was tried to be determined by using Corylus colurna L. annual tree rings, which was cut at the end of 2020 in Kastamonu province, Türkiye. Within the scope, the heavy metal concentrations in the bark and inner bark were also compared with the heavy metal concentrations in the woods, and the directional variation of the heavy metal concentrations was also evaluated. As a result, there was a significant difference between wood and bark (p<0.05) except for the north direction of Li element, and the concentrations obtained in the woods were much higher than those in the bark. In the annual rings, the variation of the Li concentration in all directions, except for the west direction, is significant (p<0.05). However, Li concentration generally varies in a narrow range, and this can be interpreted as the Li element being transferred between woods in C. colurna.
Keywords: 13. Climate action; 11. Sustainability; 15. Life on land; 6. Clean water